A study on determinants that influence global copper price / Hazwani Jasmani - Jasmani, Hazwani (Bachelor of Science (Hons) Statistics, 2014)
Copper is one of base metal among commodities and considered as the actual inputs used in manufacturing, construction and production. It is because copper is the main item for companies to build their products or expand their facilities. Copper also being founded to predict the health of economy. There are three main objectives focus in this study which is to identify the pattern of time series data for copper price range from January 1996 until April 2014, to identify the relationship between global copper price and the determinants, and to identify which factors most contribute significantly to the changes of global copper price. An econometric modelling approach was used to analyse modelling in this study. It was found that the patterns for copper price are cyclical component, trend component and random shock. Then, the researcher used Scatter Plot and Pearson Correlation Coefficient to identify the relationship between global copper price and the variables involved to establish the result. This indicates that there is a strong negative relationship between global copper price and US Dollar. In addition, this study also proved that there is strong positive relationship between copper price with China demand and Chile supply for copper. However, the relationship of global copper price with industrial production from US, Japan, China and Eurozone established weak positive relationship. For the global copper price and volatility index, it is found that weak negative relationship between them. Moreover, the result also shows that there are three significant variables that contribute to the model performance which are US Dollar, Chile Supply and Eurozone Industrial Production